Successful Management of Schizoaffective Disorder (Manic Type) in a Pregnant Woman with Electroconvulsive Therapy: A Case Report - Kusumadewi, Andrian Fajar; Anindita Fabiola Rahma; Dyah Utami Nugraheni; Karina Safira Gozali; Kevin Thenedi; Milleninda Pasca Yushinta; Nabilah El Husna; Noka Yogahutama (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Schizoaffective disorder is a chronic mental health condition characterized by the presence of both psychotic and mood symptoms. Managing schizoaffective disorder during pregnancy presents unique challenges due to the potential risks of pharmacotherapy to the developing fetus. This case report describes the successful management of a pregnant woman with schizoaffective disorder (manic type) using electroconvulsive therapy (ECT). Case presentation: A 31-year-old woman, G2P1A0 with a gestational age of 26 weeks, was admitted to the psychiatric ward with symptoms of mania and psychosis, including disorganized behavior, threats of violence, suspicious delusions, auditory hallucinations, and visual illusions. Her symptoms had worsened after discontinuation of her antipsychotic medication due to pregnancy. She was diagnosed with schizoaffective disorder, manic type. Due to the potential risks of antipsychotic medication to the fetus, ECT was initiated. The patient responded well to ECT, with a significant reduction in her manic and psychotic symptoms. She was able to continue her pregnancy safely, and delivered a healthy baby at term. Conclusion: This case report highlights the effectiveness and safety of ECT in managing schizoaffective disorder during pregnancy. ECT can be considered a valuable treatment option for pregnant women with severe mental illness when the risks of pharmacotherapy outweigh the benefits.